The Role of the District Government in Implementing E-Government-Based Services for the Community (A Study in Cikeusik District, Pandeglang Regency) - Mohamad Iyos Rosyid; Hasyim Adnan; Sindi Sahara (HK-Publishing, 2025)
The implementation of E-Government in Cikeusik District faces several challenges that serve as the focus of this study. Despite efforts to integrate digital technology into public services, issues persist regarding universal access to technology, disparities in understanding how to use digital platforms, and infrastructure that does not yet fully support the system. This study employs a descriptive qualitative method, with the district government and the local community serving as the subjects. These subjects were selected using a purposive sampling technique. The findings indicate that the Cikeusik District government has not fully implemented electronic-based population administration services in accordance with prevailing government regulations. Although there have been attempts to operate an E-Government system, its implementation remains incomplete and appears superficial. Current services have not yielded significant impacts regarding effectiveness, efficiency, or interactivity between the government and the community. From the community's perspective, the existing E-Government services have failed to provide the expected convenience. In fact, some residents perceive the system as disadvantageous due to difficulties in accessing applications, limited technological literacy, and a lack of adequate technical support. Therefore, despite the good intentions behind implementing E-Government, the district government needs to conduct evaluations and improvements to ensure that electronic-based services operate more effectively, efficiently, and interactively, thereby truly benefiting the community. Keywords: E-Government, Public Service, District Government